Weaving Identity into Professional Fashion: Cultural Expression and Garment Innovation among Career Women in Bolgatanga, Ghana - Asobayire, Joyce; Aboagyewaa-Ntiri, Josephine; Saana, Alfredina (Advances in Social Sciences Research Journal, 2025)
Fashion operates as a critical medium through which individuals negotiate identity, culture, and modernity. This study explored how career women in Bolgatanga, Ghana, express cultural identity through fashion and examined the integration of indigenous materials into professional attire. Guided by sociological, cultural identity, and cultural representation theories, the study employed a descriptive cross-sectional design with a mixed-method approach. Data were collected from 150 career women (teachers and bankers) through questionnaires and from 10 fashion designers through semi-structured interviews. Quantitative data were analysed using descriptive statistics, while qualitative insights were thematically examined. Findings revealed that career women value fashion as a means of affirming identity and cultural pride, though institutional dress codes often restrict everyday cultural expression. African prints dominate Friday wear, while garments such as fugu and smocks are reserved for ceremonial occasions. A practical design component integrated fugu, leather, and calabash into three professional garments. Evaluation of these garments demonstrated high acceptability, with preferences leaning toward designs that subtly balanced cultural symbolism and professional aesthetics. The sheath dress with fugu side panels and calabash buttons emerged as the most preferred. The study concludes that culturally inspired professional fashion offers a pathway for cultural preservation, women’s empowerment, and creative industry development. It recommends greater institutional flexibility in dress codes and enhanced collaboration between designers and artisans to sustain indigenous craft traditions while advancing professional fashion in Ghana.